My Trip Pal: an Android application for tracking travel - Swapna, Bojanki (Kansas State University, 2014)
Smartphones have become an integral part of everyday life and a study conducted by Kantar World panel ComTech (11/2012 – 02/2013) showed sales of all Android phones outpaced the iPhone by a hefty margin: 52.1 percent to 43.5 percent. Moreover, Android is the OS for most of the mobiles like HTC, Google, Samsung, Sony, Motorola etc. As Steve Jobs said “It’s really hard to design products by focus groups. A lot of times, people don’t know what they want until you show it to them.” There are a lot of common people out there who travel often and book tickets on various websites; i.e., a person like me travels very often and books ticket on a website which provides for the cheapest price. Most of the time the destinations might match and they want to keep track of the websites the tickets are booked, track the dates travelled to a place, track the price and various other details as it gets difficult to remember all details. Moreover, it is hectic to browse through each and every website and check the previous travel. Similarly, if one travels on quite a number of trips via car, one might want to keep track of those details, too. Hence to track all of these, it would be very convenient if there was an application which can take in all details of personal trips so that you can refer back to them whenever you want to do so. MyTripPal is an Android application where a user can save past trips and future trips via flight or car and a user can enter in all details and save trips. For a future trip, users can be reminded via alarm on a date and time he chooses while entering the trip details in the application. Autofill option is given while entering the source and destination where these are prompted from the values that are entered earlier in previous trips. Google maps navigation option is given which provides the route from the source to the destination. The user can also search for the trips and there is an Upcoming Trips tab which lists all future trips via car or flight.
MyTripPal
Keywords: Android; MyTripPal; trip; Computer Science (0984)